IMPROVED LMD AND ITS APPLICATIONS ON GEAR FAULT DIAGNOSIS - ZHENG XiaoXia; LIU PengHui; ZHOU RongCheng; FU Yang (Jixie qiangdu)
As one of the key components of mechanical drive system,gear fault holds a large proportion in the transmission system fault,its working status directly affect the performance of the equipment.Aiming at the characteristics of the gear fault signal mostly for the non-stationary modulation signal,proposed based on spline and an improved algorithm of LMD continuation boundary characteristics,through the adoption of cubic spline interpolation,the signal of extreme value point interpolation to get the upper and lower envelope,and local characteristic scale boundary continuation method is adopted to reduce the endpoint effect,improve the precision and computational efficiency of decomposition.The simulation study of simulated signals and experimental platform of fault data show that improved LMD algorithm is proposed in this paper that decomposition PF components is smaller error compared with the ideal value,shorter time decomposition,accurately analyzing the fault characteristics of the gear.